2017
DOI: 10.1186/s12913-017-2358-1
|View full text |Cite
|
Sign up to set email alerts
|

Are physicians aware enough of patient radiation protection? Results from a survey among physicians of Pavia District– Italy

Abstract: BackgroundRadiological practices are the first anthropic sources of ionizing radiation exposure of the population. However, a review of recent publications underlines inadequate doctors’ knowledge about doses imparted in medical practices and about patient protection that might explain unnecessary radiological prescriptions. We investigated the knowledge of the physicians of Pavia District (Italy) on the risk of radiation exposure.MethodsA cross sectional study was performed involving the Medical Association o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
2
12
2
4
Order By: Relevance
“…This may be attributed to the precision of the questions; radiation specialists should be able to answer such questions, while the knowledge of physician is expected to be general. Unlike previous studies [13], [25], [29], [32], this study revealed a poor level of knowledge among physicians about ionizing radiation.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This may be attributed to the precision of the questions; radiation specialists should be able to answer such questions, while the knowledge of physician is expected to be general. Unlike previous studies [13], [25], [29], [32], this study revealed a poor level of knowledge among physicians about ionizing radiation.…”
Section: Discussioncontrasting
confidence: 99%
“…This inconsistency between the reported and actual level of knowledge could indicate that doctors are not aware of their deficiencies. These findings are consistent with previous studies in other countries [13], [25], [29], [31], [32], [33], which also revealed a low level of radiation knowledge among referring physicians. This study found that only 31.7% of the respondents had previous courses on radiation doses in diagnostic imaging which may be a contributing factor in the overall poor knowledge base.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of this study showed that, most participants had a high level of knowledge on radiation in terms of the types, benefits and effects (Table 3). In contrast, a study by Chun-sing et al, and others showed that physicians and interns had poor knowledge of radiation related to radiological imaging [23][24][25][26][27][28][29][30][31]. These studies considered all HCWs including radiologists.…”
Section: Discussionmentioning
confidence: 99%